Management of the Outpatient Registration Service in Marthen Indey Hospital Jayapura - Astrodita Adya Seta (Lafadz Jaya Publisher, 2024)
When patients visit a hospital, the first place they go to is the outpatient registration area. This is where patients form their first impression of the hospital, so the process must run smoothly. Unfortunately, this is often not the case. Patients may experience long wait times, queue number issues, and computer errors, which can lead to frustration and complaints. To gain a better understanding of the outpatient registration process, we conducted a qualitative research study at Marthen Indey Hospital in Jayapura. We interviewed staff and observed the process in action. Our findings showed that patients had to register in person, and there were several issues with the system. For example, the queuing machine didn't differentiate between polyclinics, which caused long queues to build up. This, in turn, increased wait times for patients. Despite these challenges, we found that the outpatient registration process at Marthen Indey Jayapura Hospital was in line with standard operating procedures for new and returning patients. However, we believe that there is room for improvement. By addressing these issues and finding solutions, we can improve the patient experience and ensure that the hospital provides the best possible care.